Occurrence of methane-oxidizing bacteria and methanogenic archaea in earth’s cave systems—A metagenomic analysis - Allenby, Alexander; Cunningham, Mark R.; Hillebrand-Voiculescu, Alexandra; Comte, Jean-Christophe; Doherty, Rory; Kumaresan, Deepak (Frontiers in Ecology and Evolution, 2022)
Karst ecosystems represent up to 25% of the land surface and recent studies highlight their potential role as a sink for atmospheric methane. Despite this, there is limited knowledge of the diversity and distribution of methane-oxidizing bacteria (MOB) or methanogens in karst caves and the subsurface environment in general. Here, we performed a survey of 14 shotgun metagenomes from cave ecosystems covering a broad set of environmental conditions, to compare the relative abundance and phylogenetic diversity of MOB and methanogens, targeting biomarker genes for methane monooxygenase (pmoA and mmoX) and methyl coenzyme M reductase (mcrA). Taxonomic analysis of metagenomes showed 0.02% to 1.28% of classified reads were related to known MOB, of which Gammaproteobacterial MOB were the most abundant making up on average 70% of the surveyed caves’ MOB community. Potential for biogenic methane production in caves was also observed, with 0.008 %– 0.39 % of reads classified to methanogens and was dominated by sequences related to Methanosarcina. We have also generated a cave ecosystems protein database (CEPD) based on protein level assembly of cave metagenomes that can be used to profile genes of interest.